EFFECT OF WATER-SAVING IRRIGATION TECHNOLOGIES ON SOIL AGROCHEMICAL PARAMETERS IN SOYBEAN CULTIVATION - S. X. Isayev; Z. Z. Qodirov; M. M. Avliyoqulov; M. Shodmonova (Journal Park Publishing, 2023)
The scientific research illustrates that in the conditions of irrigated meadow-alluvial soils of the Bukhara region, methods of irrigation of late soybean varieties "Baraka" and "Uzbek-6" and their soil structure, as well as the effect of irrigation methods on the agrochemical parameters of the soil will be discussed. According to the results of the conducted scientific research, it was found that the agrochemical parameters of the soil in the soybean field grown on the basis of the technologies of drip irrigation and drip irrigation under the film are relatively higher than those of horizontal irrigation.
Keywords: irrigation methods, drip irrigation method, irrigation rate and order, soil moisture depth, soybean root system, soybean yield, irrigation technique